(untitled) (Texas Journal of Philology, Culture and History, 2022)
The competence-based model of training specialists aims not only to perform specific functions of education, but also to implement integrated requirements for the result of the educational process. Communicative competence implies the formation of some special skills: the ability to establish contact, listen, "read" non-verbal language of communication, build a conversation, formulate questions. It is also important for the doctor to control his own emotions, the ability to maintain confidence, control his reactions and behavior in general.